Pemikiran Ekonomi Islam dalam Era Kontemporer: Antara Etika, Keadilan, dan Tantangan Globalisasi - Ahmad Fadhil Fayyadh; Nur Anis Aulia; Fauzan Aidul Fitra (Journal of Islamic Economic Studies, 2025)
Contemporary Islamic economic thought has emerged as an intellectual response to the complexities of the modern global economy, particularly the dominance of capitalism, persistent economic inequality, and ethical deficiencies within prevailing economic systems. This article aims to examine the development and core characteristics of contemporary Islamic economics, its distinction from classical Islamic economic thought, as well as its theoretical implications and future direction within the broader landscape of global economic discourse. Employing a qualitative-descriptive approach through library research, this study analyzes the works of modern Islamic economic thinkers alongside relevant academic literature. The findings indicate that contemporary Islamic economics emphasizes the integration of market mechanisms with Islamic ethical values by positioning maqāṣid al-sharīʿah as a central analytical framework. While differing from classical Islamic economics in terms of context and methodological approach, its ultimate normative objective remains the pursuit of just and holistic human welfare. The study further identifies conceptual and implementation challenges that reflect an ongoing evolutionary process rather than a stagnation of thought. Theoretically, this research reinforces Islamic economics as a value-based economic paradigm, while practically it offers insights for developing more equitable, humane, and sustainable economic policies in the modern era.